Utilization of a Cardiometabolic Health Nurse – a Novel Strategy to Manage Comorbid Physical and Mental Illness. Issue 1 (2014) - Happell, Brenda; Stanton, Robert; Scott, David
Background: Comorbid chronic illnesses, such as cardiovascular disease, respiratory conditions, and type 2 diabetes are common among people with serious mental illness. Management of comorbid illness in the mental health setting is sometimes ad hoc and poorly delivered. Use of a cardiometabolic health nurse (CHN) is proposed as one strategy to improve the delivery of physical health care to this vulnerable population. Objective: To report the CHN's utilization of primary care and allied health referrals from a trial carried out in a regional community mental health service. Design: Feasibility study. Mental health consumers were referred by their case manager or mental health nurse to the CHN. The CHN coordinated the physical health care of community-based mental health consumers by identifying the need for, and providing referrals to, additional services, including primary care, allied health, and community-based services. Results: Sixty-two percent of participants referred to the CHN received referrals for primary care, allied health, and community-based services. Almost all referrals received follow-up by the CHN. Referrals were most commonly directed to a general practitioner and for nurse-delivered services. Conclusion: The CHN role shows promise in coordinating the physical health of community-based mental health consumers. More studies on role integration and development of specific outcome measurement tools are needed.